Battery and electric device comprising same

By controlling specific material composition and structural parameters in the battery case, the problem of difficult balance of the molding performance, deformation risk and energy density of the battery case in the prior art is solved, and a safer and more efficient battery design is achieved.

CN119542633APending Publication Date: 2025-02-28CALB GROUP CO LTD

Patent Information

Application Number
CN202411760539.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to balance the processing performance of the battery case during the molding process, the ability to resist deformation risks caused by cell expansion, and the battery energy density.

Method used

By controlling the sum of distances a between the end walls at both ends of the housing and the end faces of the battery cell, the thickness d of the first end wall, and the contents b and c of Ti and Nb, the conditions of 0.15≤a/[d×(b+c)]≤300 are met to balance the deep-ttracting processing performance and deformation risks of the shell and ensure the energy density of the battery.

Benefits of technology

It realizes that the shell can maintain good processing performance during the deep drawing molding process, and reduce the risk of deformation caused by cell expansion, ensuring the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542633A_ABST
    Figure CN119542633A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a battery and an electric device comprising the battery, the battery comprises a shell and a battery cell arranged in the shell, the material of the shell comprises steel, the steel comprises Ti, Nb and Cr, based on the total mass of the steel, the mass percentage content of Cr is larger than or equal to 16 wt.%, and based on the total mass of the steel, the mass percentage content of Nb is larger than or equal to 20 wt.%. The shell comprises a side wall and end walls, the end walls comprise a first end wall and a second end wall located at the two ends of the side wall, and the two ends of the battery cell comprise a first end face close to the first end wall and a second end face close to the second end wall; the shell satisfies the following relational expression: 0.15 < = a / [d * (b + c)] < = 300. By controlling the sum a of the distances between the end walls at the two ends of the shell and the end faces at the two ends of the battery cell, the thickness d of the first end wall and the relation between the content b and the content c of Ti and Nb, the processability of the shell in the forming process and the capacity of the shell for resisting the deformation risk caused by battery cell expansion are balanced.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of CN 202411556208.1 (the application date is November 4, 2024, the application number is 202411556208.1, and the name of the invention is a battery and an electrical device including the battery). Technical Field

[0002] The present invention relates to the technical field of batteries, and in particular to a battery and an electrical device comprising the battery. Background Art

[0003] The battery case is not only a physical protective barrier for the battery, preventing the internal components of the battery from being affected by the external environment (such as humidity, dust, vibration, etc.), but also ensures the safety of the battery during use. The battery case is usually made of materials with certain strength, corrosion resistance and insulation properties to meet the needs of the battery in various working environments. Especially for power batteries used in new energy vehicles, battery safety is even more important.

[0004] At present, metal deep drawing is one of the important forming methods for manufacturing battery shells. It is a process that uses the plasticity of metal materials to further stretch and deform the materials under specific pressure conditions to form the desired shape. Deep drawing is widely used in automobile manufacturing, aerospace, electronic equipment and other fields due to its advantages of high processing efficiency, low cost and stable quality.

[0005] In order to ensure the processing performance of the metal during the deep drawing process, the material needs to have a certain ductility and plastic deformation ability. However, the thickness of the shell after deep drawing will become thinner. The high plastic deformation ability of the material will increase the risk of deformation of the shell after forming, thereby affecting the safety of the battery. In particular, when the battery shell is manufactured by deep drawing, the battery cells in the shell will expand during the charging and discharging process, resulting in a greater risk of deformation of the shell. If the strength of the battery shell is increased by increasing the thickness of the shell, the cost of the battery may increase, and the increase in the battery's own weight will reduce the battery's energy density. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the prior art in balancing the three performances of shell molding processing performance, the shell's ability to resist the risk of deformation caused by cell expansion, and battery energy density, and to provide a battery and an electrical device including the battery.

[0007] To achieve the above object, in a first aspect of the present invention, the present invention provides a battery, comprising a shell and a battery cell arranged in the shell, wherein the material of the shell comprises steel, the components of the steel comprise Ti, Nb and Cr, wherein the mass percentage of Cr is ≥16wt.% based on the total mass of the steel; the shell comprises a side wall and an end wall, the end wall comprises a first end wall and a second end wall located at both ends of the side wall, the two ends of the battery cell comprise a first end face close to the first end wall and a second end face close to the second end wall; the first end wall is integrally formed with the side wall;

[0008] The shell satisfies the following relationship: 0.15≤a / [d×(b+c)]≤300;

[0009] Wherein, a is the sum of the distance from the first end surface to the first end wall and the distance from the second end surface to the second end wall, in mm;

[0010] d is the thickness of the first end wall, in mm;

[0011] b is the mass percentage of Ti based on the total mass of steel, in wt.%;

[0012] c is the mass percentage of Nb based on the total mass of steel, in wt.%.

[0013] As a preferred embodiment of the present invention, the shell satisfies the following relationship: 1≤a / [d×(b+c)]≤200.

[0014] As a preferred embodiment of the present invention, the range of b+c is 0.2-0.8 wt.%.

[0015] As a preferred embodiment of the present invention, the range of b+c is 0.25-0.5 wt.%.

[0016] As a preferred embodiment of the present invention, the range of b is 0.05-0.2 wt.%.

[0017] As a preferred embodiment of the present invention, the range of c is 0.17-0.5 wt.%.

[0018] As a preferred embodiment of the present invention, the range of d is 0.15-1.2 mm.

[0019] As a preferred embodiment of the present invention, the range of a is 0.1-10 mm.

[0020] As a preferred embodiment of the present invention, the battery is a cylindrical battery.

[0021] As a preferred embodiment of the present invention, the range of a is 0.5-10 mm.

[0022] As a preferred embodiment of the present invention, the battery cell is provided with a core winding hole, and the battery satisfies the following relationship: 0.4≤S×a≤600;

[0023] Wherein, S is the area of ​​the core hole, unit: mm 2 .

[0024] As a preferred embodiment of the present invention, the battery is a quadrangular prism battery.

[0025] As a preferred embodiment of the present invention, the range of a is 0.1-8 mm.

[0026] As a preferred embodiment of the present invention, when the aspect ratio of the shell is not less than 2, the range of b+c is 0.2-0.7 wt.%.

[0027] As a preferred embodiment of the present invention, the battery cell comprises a positive electrode tab and a negative electrode tab, the positive electrode tab or the negative electrode tab is electrically connected to the shell, and the mass percentage of Cr is 16-30wt.%.

[0028] As a preferred embodiment of the present invention, the positive electrode tab and the negative electrode tab are both arranged on the first end face or the second end face of the battery cell, and the range of a is 0.5-10 mm.

[0029] As a preferred embodiment of the present invention, the positive electrode tab and the negative electrode tab are respectively arranged on the first end surface and the second end surface of the battery cell, and the range of a is 0.2-8 mm.

[0030] An electrical device comprises the battery as described above.

[0031] The beneficial effects of the present invention are:

[0032] The present invention balances the processing performance of the shell during the molding process and the shell's ability to resist deformation risk caused by the expansion of the battery cell by controlling the sum of the distances a between the end walls at both ends of the shell and the end faces at both ends of the battery cell, the thickness d of the first end wall, and the relationship between the contents b and c of Ti and Nb, so that the shell is easy to be deep-drawn and molded, and has a certain ability to resist deformation after the shell is molded, thereby avoiding deformation of the shell due to expansion of the battery cell during the charging and discharging process, and ensuring the safety of the battery. At the same time, it ensures that the energy density of the battery is not too small, and avoids reducing the energy density of the battery by making a or d too large in order to reduce the deformation risk of the battery shell. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the overall structure of the housing of Example 1;

[0034] Figure 2This is a schematic diagram of the internal structure of the housing of Example 1;

[0035] Figure 3 This is a schematic diagram of the overall structure of the shell of Example 29.

[0036] The illustrations are as follows:

[0037] 1-shell, 11-first end wall, 12-second end wall, 13-side wall, 2-battery core, 21-core hole. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0040] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0041] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0042] An embodiment of the present invention provides a battery, comprising a shell 1 and a battery cell 2 arranged in the shell 1, wherein the material of the shell 1 comprises steel, and the components of the steel include Ti, Nb and Cr, wherein the mass percentage of Cr is ≥16wt.% based on the total mass of the steel; the shell 1 comprises a side wall 13 and an end wall, and the end wall comprises a first end wall 11 and a second end wall 12 located at both ends of the side wall 13, and both ends of the battery cell 2 comprise a first end face close to the first end wall 11 and a second end face close to the second end wall 12; the first end wall 11 and the side wall 13 are integrally formed;

[0043] The housing 1 satisfies the following relationship: 0.15≤a / [d×(b+c)]≤300;

[0044] Wherein, a is the sum of the distance from the first end surface to the first end wall 11 and the distance from the second end surface to the second end wall 12, in mm;

[0045] d is the thickness of the first end wall 11, in mm;

[0046] b is the mass percentage of Ti based on the total mass of steel, in wt.%;

[0047] c is the mass percentage of Nb based on the total mass of steel, in wt.%.

[0048] As the battery shell 1 needs to meet certain corrosion resistance, the corrosion resistance of the shell 1 of the steel shell battery is improved by Cr mass percentage ≥ 16wt.%, but the hardness of the shell 1 will increase and the toughness and plasticity will decrease after the mass percentage of Cr increases, and the deep drawing performance will deteriorate, which increases the risk of fracture of the shell 1 during the deep drawing process, resulting in a decrease in the manufacturing yield and performance of the shell 1. Therefore, the deep drawing performance of steel is improved by adding Ti and Nb to ensure the rapid forming and yield of the shell 1.

[0049] The shell 1 is made of steel and formed by deep drawing. Its Ti (titanium) content b and Nb (niobium) content c affect the plastic deformation ability of the shell 1. If the total content of Ti and Nb is too small, the plastic deformation ability of the steel is poor. The shell 1 is easily damaged during stamping, resulting in an increase in the defect rate. However, the content of Ti and Nb cannot be too large. Although the plastic deformation ability is improved by increasing the content of Ti and Nb within a certain range, which is beneficial to the deep drawing of the shell 1, the risk of deformation of the shell 1 due to stress will also increase. In particular, the thinner the wall thickness d of the end wall of the shell 1 after forming, the greater the risk of deformation. Moreover, if the content of Ti and Nb is too large, they will form coarse particles with the iron element, reducing the forming performance of the steel.

[0050] The battery cell 2 will expand during charging and discharging, thereby increasing the risk of deformation of the shell 1. In particular, the end wall of the shell 1 usually integrates various components such as centralized components, and the expansion of the end wall will greatly increase the safety risk of the battery. In order to reduce or avoid deformation of the shell 1 caused by the expansion of the battery cell 2, it is necessary to control the sum of the distance between the first end face of the battery cell 2 and the first end wall 11 of the shell 1 and the distance between the second end face of the battery cell 2 and the second end wall 12 of the shell 1, that is, the total gap between the two ends of the battery cell 2 and the inner wall 13 of the shell 1. If a is too small, the shell 1 is easily deformed when the battery cell 2 expands. If a is too large, the internal space occupancy rate of the shell 1 will be low, reducing the energy density of the battery. The battery cell 2 includes a battery cell 2 body and a pole ear. The first end face and the second end face refer to the end faces of the battery cell 2 body. The pole ear is arranged on the end face of the battery cell 2 body. Therefore, the distance between the first end face and the first end wall 11 refers to the distance from the battery cell 2 body to the first end wall 11, rather than the distance from the pole ear to the first end wall 11. The distance from the second end face to the second end wall 12 also refers to the distance from the battery cell 2 body to the second end wall 12.

[0051] Therefore, when a is relatively large, there is a large space between the battery cell 2 and the end wall of the shell 1, and the shell 1 is not easily deformed due to the expansion of the battery cell 2, so that b+c can also be relatively large to obtain better plastic deformation ability and improve deep drawing processing performance. However, a cannot be made too large to avoid deformation of the shell 1 due to the expansion of the battery cell 2, because a too large a will lead to a decrease in the volume energy density of the battery.

[0052] The first end wall 11 is formed integrally with the side wall 13. When the shell 1 is formed by deep drawing, an opening is required for the punch to enter. The opening is usually one of the end walls of the battery. This end wall is formed integrally with the side wall 13, while the other end wall is formed separately and fixedly connected to the side wall 13 by welding, riveting, bonding, etc. In the present invention, the first end wall 11 refers to the end wall formed integrally with the side wall 13, and the second end wall 12 refers to the end wall fixedly connected to the side wall 13 after being formed separately. Since the first end wall 11 and the side wall 13 are formed integrally by deep drawing, the thickness that can be formed of the first end wall 11 is related to the deep drawing performance of steel. At the same time, the greater the thickness of the first end wall 11, the greater its anti-deformation ability, and the smaller the risk of fracture during the forming process of the shell 1. Therefore, the present invention limits the thickness of the first end wall 11 instead of the thickness of the second end wall 12.

[0053] When d is larger, that is, the thickness of the first end wall 11 is larger, the risk of deformation of the shell 1 is smaller, the stretching ratio of the shell 1 is smaller, and the risk of breakage during the molding process is reduced. At this time, a and b+c can be relatively reduced, but d cannot be too large. If d is too large, the mass energy density of the battery will be too large and the cost will be too high.

[0054] When d is small, that is, the wall thickness of the first end wall 11 is small, the stretching of the shell 1 is relatively large, and the risk of breakage during the forming process is higher. In order to improve the forming performance of the shell 1, b+c should be appropriately increased, but this will increase the risk of deformation of the shell 1. Therefore, in order to reduce the risk of deformation of the shell 1, a should also be appropriately increased.

[0055] In summary, by making the sum a of the distance from the first end face to the first end wall 11 and the distance from the second end face to the second end wall 12, the thickness d of the first end wall 11, the mass percentage b of Ti, and the mass percentage c of Nb satisfy: 0.15≤a / [d×(b+c)]≤300, the shell 1 can not only meet the plastic deformation capacity required for deep drawing processing, but also reduce the risk of deformation of the shell 1 after forming, avoid the risk of deformation of the shell 1 due to expansion of the battery cell 2, and at the same time ensure that the energy density of the battery is not too small.

[0056] In one embodiment, the first end wall 11 is integrally formed with the housing 1, the second end wall 12 may be a separate cover plate, and the second end wall 12 and the circumferential side wall 13 of the housing 1 may be welded, riveted, bonded, etc. The material of the cover plate may be the same as that of the side wall 13 and the first end wall 11.

[0057] In some embodiments of the present invention, the specific selection of a / [d×(b+c)] can be 0.15, 0.2, 0.3, 0.5, 1, 2, 5, 8, 10, 20, 30, 50, 75, 100, 120, 150, 180, 200, 220, 250, 270, 280, 300, or it can be an interval range formed by any two of the above values, such as 1-200, 0.2-120, 2-220, etc.

[0058] The test method of Ti, Nb and Cr content is not limited, and those skilled in the art can test Ti, Nb and Cr content according to conventional methods, such as inductively coupled plasma method, X-ray fluorescence spectrometry, etc.

[0059] The measurement method of a is as follows:

[0060] Measure the height of the battery cell 2, i.e., the maximum distance a1 from the first end face to the second end face, and measure the height inside the housing 1, i.e., the minimum distance a2 from the first end wall to the second end wall, then a = a2 - a1. In order to reduce errors, measure a1 and a2 multiple times and take their average values.

[0061] The measurement method of b is as follows:

[0062] The thickness of the first end wall 11 is measured using an ultrasonic thickness gauge. In order to reduce errors, measurements are taken at multiple different positions of the first end wall 11 of each shell 1 and the average value is taken as the thickness d of the first end wall 11 of the shell 1 .

[0063] The test method of Ti, Nb and Cr content is not limited, and those skilled in the art can test Ti, Nb and Cr content according to conventional methods. For example, inductively coupled plasma method, X-ray fluorescence spectrometry or other test methods do not affect the implementation of this solution.

[0064] Inductively coupled plasma method:

[0065] (1) Sample preparation: Stainless steel samples need to be properly pretreated, such as being dissolved in a specific acid solution to release the elements to be tested. For example, aqua regia is used to dissolve the sample, or a specific mixed acid system is used for digestion to ensure the effective release of the elements.

[0066] (2) Analysis method: The analysis method of ICP-OES mainly includes the standard curve method and the internal standard method. The standard curve method draws a relationship curve between the concentration of the standard solution and the emission intensity at the corresponding wavelength, and compares the emission intensity of the sample solution with the standard curve to obtain the content of each element in the sample. The internal standard method selects an element with similar chemical properties to the element to be measured and with a constant content in the sample as the internal standard. By comparing the emission intensity ratio of the element to be measured and the internal standard element, the influence of factors such as sample composition and experimental conditions is eliminated.

[0067] X-ray fluorescence spectrometry

[0068] (1) Sample preparation: First, the stainless steel sample needs to be properly processed to facilitate X-ray penetration and stimulate fluorescence. This may include cutting, grinding, polishing and other steps to ensure that the sample surface is flat and free of contamination.

[0069] (2) X-ray excitation: High-energy X-rays are used to irradiate the sample surface to stimulate the characteristic X-ray fluorescence of each element. The wavelength or energy characteristics of these fluorescence spectra correspond to the type of element, so it is possible to determine which elements are contained in the sample.

[0070] (3) Spectrum collection and analysis: The X-rays reflected from the sample surface and the fluorescence spectrum emitted are collected by a spectrometer. The type and content of the element can be determined by the position and intensity of the characteristic spectral lines.

[0071] (4) Matrix effect correction: Due to the interaction between various elements in stainless steel (matrix effect), the collected spectral data needs to be corrected to eliminate the influence of this interaction on the analysis results and improve the accuracy of the analysis.

[0072] (5) Interpretation of results: Based on the corrected data, the content of each element in the stainless steel can be calculated, and then its performance and quality can be evaluated.

[0073] In one embodiment, the housing 1 satisfies the following relationship: 1≤a / [d×(b+c)]≤200.

[0074] In this solution, the shell 1 that satisfies the above relationship not only meets the plastic deformation capacity required for deep drawing processing, but also has a lower degree of deformation of the shell 1 due to the expansion of the battery cell 2.

[0075] In one embodiment, the range of b+c is 0.2-0.8 wt.%.

[0076] In some embodiments of the present invention, the specific selection of b+c can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, or it can be an interval range formed by any two of the above values, such as 0.25-0.5, 0.3-0.7, 0.2-0.6, etc.

[0077] In one embodiment, the range of b is 0.05-0.2 wt.%.

[0078] In some embodiments of the present invention, the specific selection of b can be 0.05, 0.06, 0.07, 0.08, 0.1, 0.12, 0.15, 0.17, 0.18, 0.19, 0.2, or it can be an interval range formed by any two of the above values, such as 0.05-0.15, 0.07-0.2, 0.1-0.2, etc.

[0079] In one embodiment, the range of c is 0.17-0.5 wt.%.

[0080] In some embodiments of the present invention, the specific selection of c can be 0.17, 0.18, 0.19, 0.2, 0.22, 0.25, 0.28, 0.3, 0.35, 0.4, 0.45, 0.48, 0.5, or it can be an interval range formed by any two of the above values, such as 0.17-0.4, 0.2-0.4, 0.25-0.5, etc.

[0081] Ti and Nb are both stabilizing elements of carbon and nitrogen, and can combine with carbon and nitrogen to form TiC, TiN or NbC, NbN, which inhibits the formation of chromium carbon and nitride in steel and improves the intergranular corrosion resistance of stainless steel. At the same time, Ti and Nb are both forming elements of ferrite. A proper amount of Ti in steel can refine the ferrite weld structure and improve the weld plasticity and formability. However, excessive addition of Ti will reduce the forming rate of the material. At the same time, Ti mainly exists in the form of precipitated phases such as TiN. The solid solubility product of TiN is very low, so it begins to precipitate before solidification. This non-uniform nucleation point promotes the excessive proportion of equiaxed crystals in the solidification structure, thereby obtaining good deep drawing performance. The solid solution Nb can promote the formation of γ+α two-phase region texture in steel. A small amount of this texture is beneficial to improve the deep drawing performance. However, too high Nb content will lead to the formation of Fe2Nb hard phase in the steel, which will reduce the elongation and deep drawing performance of the material. Excessive nitride (NbN) formed by Nb and nitrogen will also reduce the thermoplasticity of the steel.

[0082] The mass percentage of Ti is the percentage of the mass of Ti in the total mass of steel, and the mass percentage of Nb is the percentage of the mass of Nb in the total mass of steel.

[0083] In one embodiment, the range of d is 0.15-1.2 mm.

[0084] In some embodiments of the present invention, the specific selection of d can be 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, or it can be an interval range formed by any two of the above values, such as 0.2-1.0, 0.15-0.8, 0.5-1.2, etc.

[0085] In one embodiment, the range of a is 0.1-10 mm.

[0086] In some embodiments of the present invention, the specific selection of a can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, or it can be an interval range formed by any two of the above values, such as 0.2-0.8, 0.5-1.0, 0.35-0.85, etc.

[0087] In one embodiment, the battery is a cylindrical battery.

[0088] In one embodiment, the range of a is 0.5-10 mm.

[0089] The battery cell 2 will expand during the charging and discharging process, thereby exerting force on the shell 1, causing the shell 1 to deform. When the shell 1 is a cylinder, the expansion force of the battery cell 2 on the circumference of the cylindrical shell 1 is self-offsetting, so the impact force on the circumference of the shell 1 is relatively small, and the risk of lateral deformation of the cylindrical shell 1 is relatively small, while the expansion of the end face of the battery cell 2 has a greater impact on the end wall of the shell 1, and the deformation risk of the end wall of the cylindrical shell 1 is greater. Therefore, in order to reduce the deformation risk of the shell 1, for the cylindrical shell 1, the value of a can be appropriately increased, so that a sufficient gap is reserved between the battery cell 2 and the shell 1 to reduce the deformation rate of the end wall of the shell 1 caused by the expansion of the battery cell 2. Therefore, when the shell 1 is a cylinder, the lower limit of the preferred range of a is appropriately increased, and the range of a in this scheme is 0.5-10mm.

[0090] In one embodiment, the battery cell 2 is provided with a winding hole 21, and the battery satisfies the following relationship: 0.4≤S×a≤600;

[0091] Wherein, S is the area of ​​the winding core hole 21, unit: mm 2 .

[0092] The battery cell 2 includes a positive electrode sheet, a negative electrode sheet and a separator, the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet, the negative electrode sheet and the separator are wound or stacked to form the battery cell 2. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer. The material of the positive electrode current collector is not limited, as long as it has conductivity and does not cause adverse chemical changes in the battery, for example: stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel with a surface treatment of carbon, nickel, titanium, silver, etc. can be used. The current collector can also be a composite current collector, including a polymer intermediate layer, and a conductive layer arranged on both sides of the intermediate layer, and the active material layer is arranged on the surface of the conductive layer; further, the negative electrode current collector can be made of copper, stainless steel, nickel, titanium, etc. In a specific embodiment, the positive electrode current collector can be made of aluminum, and the negative electrode current collector can be made of copper.

[0093] The positive electrode active material layer includes positive electrode active materials, which include nickel-cobalt-manganese ternary materials, lithium iron phosphate materials, lithium manganese iron phosphate materials, etc.; the negative electrode active material layer includes negative electrode active materials, which include artificial graphite, natural graphite, silicon-based materials, etc.

[0094] When the battery cell 2 is wound into shape, the winding needle is used as a support for winding. After the winding is completed, the winding needle is pulled out from the battery cell 2, and a winding core hole 21 is formed at the center of the battery cell 2 due to the withdrawal of the winding needle. The winding core hole 21 can be used as a gas storage space to reduce the expansion rate of the battery cell 2, so as to reduce the deformation rate of the end wall of the shell 1 caused by the expansion of the battery cell 2. Therefore, the larger the winding core hole 21, the more gas storage space there is, and the lower the expansion rate of the shell 1 caused by the expansion of the battery cell 2, so that the a value can be appropriately reduced, thereby improving the space utilization of the shell 1 and improving the energy density of the battery.

[0095] In one embodiment, the battery is a quadrangular prism battery.

[0096] When the battery is a quadrangular prism battery, the battery housing 1 and the battery core 2 are both in the shape of a quadrangular prism.

[0097] In one embodiment, the range of a is 0.1-8 mm.

[0098] When the shell 1 is in the shape of a quadrangular prism, the area of ​​the side wall 13 of the shell 1 is usually different from that of the end walls at both ends, especially when the shape of the end wall is a rectangle, the side wall 13 includes two opposite first side walls and two opposite second side walls, the area of ​​the first side wall is greater than that of the second side wall, and at the same time, the shape of the battery cell 2 is also a quadrangular prism, and the battery cell 2 also includes two opposite first side surfaces and two opposite second side surfaces. The placement position of the battery cell 2 when located in the shell 1 is the same, the first side wall is arranged opposite to the first side surface, and the second side wall is arranged opposite to the second side surface. During the charging and discharging process of the battery cell 2, the first side surface of the battery cell 2 with the largest area expands to a greater extent, and the force exerted on the first side wall of the shell 1 is greater, so the deformation risk of the first side wall is higher.

[0099] Therefore, when the shape of the shell 1 is a quadrangular prism, the expansion of the shell 1 is not uniform, and the side of the shell 1 with the largest area expands more, and this side is usually the side wall 13 of the shell 1, and has little effect on the expansion of the end wall. Therefore, the preferred range of a can be appropriately reduced. The range of a in this scheme is 0.1-8mm.

[0100] In one embodiment, when the aspect ratio of the shell 1 is not less than 2, the range of b+c is 0.2-0.7 wt.%.

[0101] When the shell 1 is a quadrangular prism, the length and width of the shell 1 are the lengths of the long and short sides of the end wall of the shell 1. When the shell 1 is deep-drawn, it involves a process of turning a circle into a square. The larger the aspect ratio of the shell 1, the better the plastic deformation ability required for deep-drawing. However, the risk of deformation of the shell 1 due to the expansion of the battery cell 2 is higher, and the deformation resistance of the shell 1 needs to be considered. Therefore, when the aspect ratio of the shell 1 is not less than 2, the preferred range of b+c is 0.2-0.7wt.%.

[0102] In one embodiment, the battery cell 2 includes a positive electrode tab and a negative electrode tab, the positive electrode tab or the negative electrode tab is electrically connected to the shell 1, and the mass percentage of Cr is 16-30wt.%.

[0103] Regarding the forming method of the positive electrode tab and the negative electrode tab, specifically, the positive electrode sheet and the negative electrode sheet include a current collector and an active material layer, the active material layer is coated on the current collector, and the positive electrode tab and the negative electrode tab can be formed by cutting the current collector; they can also be separate conductive parts and electrically connected to the current collector; or they can be other methods that do not affect the implementation of the solution.

[0104] The battery also includes a pole assembly, which is arranged on the shell 1. Two pole assemblies can be provided and are respectively connected to the positive pole ear and the negative pole ear. However, in the present embodiment, one pole assembly is provided and is provided on the end wall of the shell 1, one of the positive pole ear and the negative pole ear is connected to the shell 1, one of the positive pole ear and the negative pole ear of the battery cell 2 is connected to the shell 1, and the other is connected to the pole assembly, such as the positive pole ear is connected to the shell 1 so that the shell 1 is positively charged, and the pole assembly is connected to the negative pole ear of the battery so that the pole assembly is negatively charged; or the positive pole ear is connected to the pole assembly of the battery so that the pole assembly is positively charged, and the negative pole ear is connected to the shell 1 so that the shell 1 is negatively charged.

[0105] The shell 1 is connected to the positive electrode tab or the negative electrode tab, so that the shell 1 serves as an electrode output terminal. The area of ​​the shell 1 used for electrical connection is larger, which can increase the flow area, and at the same time save the space of an electrode assembly so that the remaining motor assembly has enough space to be set up, simplify the battery structure, and provide space for the arrangement of other components such as the battery bus. The connection between the positive electrode tab or the negative electrode tab and the shell 1 is an electrical connection, which can be directly connected by welding or the like, or the positive electrode tab or the negative electrode tab can be connected first before the current collecting plate, and the current collecting plate is then welded to the shell 1 for indirect connection, and the welding effect is improved by the indirect connection. Other connection methods can also be used without affecting the implementation of this solution.

[0106] The positive pole ear or the negative pole ear is connected to the shell 1, and the shell 1 serves as the positive or negative electrical connection terminal. At this time, the risk of electrochemical corrosion of the shell 1 increases. In order to improve the electrochemical corrosion resistance of the shell 1, it is necessary to increase the Cr content. Cr is the main element that determines the corrosion resistance of stainless steel, which can increase the matrix electrode potential, thereby significantly improving the corrosion resistance of steel. In addition, as the main component of the oxide film, Cr helps to form a more stable oxide film and improves the oxidation resistance at high temperatures. However, after the Cr content increases, the hardness of the shell 1 increases, the plastic deformation ability of the shell 1 during molding deteriorates, and the processing performance deteriorates. If the processing performance of the shell 1 is to be improved, the content of Ti and Nb must be increased, which in turn increases the risk of deformation of the shell 1.

[0107] Therefore, controlling the mass percentage of Cr within 16-30wt.% not only ensures the corrosion resistance of the shell 1 and reduces the risk of deformation, but also avoids an increase in the risk of fracture during the molding process of the shell 1, which causes a decrease in the manufacturing yield of the shell 1.

[0108] In one embodiment, the positive electrode tab and the negative electrode tab are both arranged on the first end surface or the second end surface of the battery cell 2, and the range of a is 0.5-10 mm.

[0109] Since the positive electrode tab and the negative electrode tab are arranged on the same end of the battery cell 2, heat is concentrated, resulting in an increased risk of deformation of the end wall of the shell 1. The range of a can be appropriately increased. Therefore, the preferred range of a in this solution is 0.5-10mm.

[0110] In one embodiment, the positive electrode tab and the negative electrode tab are respectively arranged on the first end surface and the second end surface of the battery cell 2, and the range of a is 0.2-8 mm.

[0111] The positive electrode tab and the negative electrode tab are respectively arranged on the first end face and the second end face opposite to the battery cell 2, so that the heat is dispersed, the deformation risk of the end wall of the shell 1 is reduced, and the range of a can be appropriately reduced. Therefore, the preferred range of a in this solution is 0.2-8mm. The positive electrode tab can be arranged on the first end face, and the negative electrode tab can be arranged on the second end face; or the positive electrode tab can be arranged on the second end face, and the negative electrode tab can be arranged on the first end face.

[0112] In some embodiments, the steel comprises:

[0113] Fe, and the following components in percentage by mass (based on the total mass of the steel):

[0114] C: greater than 0 and less than 0.03%, Si: 0-0.75%, Mn: 0-1.0%, P: 0-0.04%, S: 0-0.03%, Cr: 16-30%, Ti: 0.05-0.2%, Nb: 0.17-0.5%, inevitable impurities 0.5%.

[0115] Another embodiment of the present invention further provides an electrical device, comprising the battery as described above.

[0116] Exemplarily, in some embodiments, the preparation process of the battery is as follows:

[0117] 1. Preparation of the shell:

[0118] (1) Preparation of steel: smelting the molten steel to remove impurities, and fine-tuning the target chemical composition required by the shell 1 to obtain the molten steel with the above-mentioned composition, and then casting to obtain a steel ingot;

[0119] (2) Preparation of blanks: rolling the steel ingots into coils, and then cutting the coils into plates of appropriate sizes;

[0120] (3) Deep drawing: The sheet is placed in a suitable die and fixed, and then the punch is pressed against the die with a certain force, and the drawing is repeated until the shell 1 is formed.

[0121] (4) Finishing: The excess material in the deep drawing process is cut off and trimmed to ensure that the burrs and flatness of the cut part meet the requirements; thus, the shell 1 is obtained.

[0122] 2. Preparation of Lithium-ion Batteries

[0123] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode to play an isolating role, and then wound to obtain a bare battery cell 2;

[0124] The battery cell 2 is placed in the shell 1 prepared as above, and the second end wall 12 and the shell 1 are connected together by laser welding; after drying, the electrolyte is injected into the bare battery cell 2, formed, and constant in volume to obtain a prepared lithium-ion battery.

[0125] The positive electrode sheet, separator, negative electrode sheet and electrolyte may be conventional ones in the art; they may be conventional commercial products or they may be prepared by themselves using conventional preparation methods in the art.

[0126] Specific examples further illustrate the present invention:

[0127] Embodiment 1-17:

[0128] Embodiments 1-17 respectively provide a battery, such as Figure 1 and Figure 2As shown, the housing 1 is cylindrical in shape.

[0129] The material chemical components of the shell 1 include: C, Si, Mn, P, S, Ti, Nb, Cr and Fe; wherein the mass percentages of C, Si, Mn, P and S are as follows: C: 0.03%, Si: 0.7%, Mn: 0.95%, P: 0.04%, S: 0.03% based on the total mass of the steel;

[0130] The mass percentages of Cr, Ti, and Nb are shown in Table 1;

[0131] The rest is iron.

[0132] The battery is prepared as follows:

[0133] 1. Preparation of the shell

[0134] (1) Preparation of steel: smelting the molten steel to remove impurities, and fine-tuning the target chemical composition required by the shell 1 to obtain the molten steel with the above-mentioned composition, and then casting to obtain a steel ingot;

[0135] (2) Preparation of blanks: rolling the steel ingot into coils, adjusting the size, gap and rotation speed of the rolling mill rolls to adjust the thickness of the coils during the rolling process, so as to prepare the shells 1 with different thicknesses d of the first end wall 11, and then cutting the coils into plates of appropriate sizes;

[0136] (3) Deep drawing: The sheet is placed in a suitable die and fixed, and then the punch is pressed against the die with a certain force, and the drawing is repeated until the shell 1 is formed. The formed shell 1 is cylindrical and has a volume of 10048mm 3 .

[0137] (4) Trimming: Remove and trim the excess material during the deep drawing process to ensure that the burrs and flatness of the cut meet the requirements.

[0138] 2. Preparation of positive electrode

[0139] The positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O3, conductive agent acetylene black and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The system is stirred in a vacuum mixer until it becomes uniform to obtain positive electrode slurry. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain positive electrode sheets.

[0140] 3. Preparation of negative electrode sheet

[0141] The negative electrode active material, conductive agent (SP) and binder are mixed in a certain mass ratio (97:1:1), wherein the negative electrode active material includes artificial graphite and silicon carbon material, and the ratio of artificial graphite: silicon carbon = 92:5. Then add deionized water as a solvent, stir until the system is uniform under the action of a vacuum mixer, and obtain the negative electrode slurry. The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain the negative electrode sheet.

[0142] 4. Preparation of electrolyte

[0143] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, FEC is added according to the embodiment and the comparative example, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0144] 5. Preparation of diaphragm

[0145] In this embodiment, a polyethylene film is selected as the separator, and the polyethylene film is cut to form the separator.

[0146] 6. Preparation of lithium-ion batteries

[0147] The positive electrode sheet, separator and negative electrode sheet are cut into suitable sizes and stacked in the order of positive electrode sheet-separator-negative electrode sheet, so that the separator is between the positive electrode sheet and the negative electrode to play an isolating role, and then wound to obtain a bare battery cell 2, and the height of the wound battery cell 2 is a1.

[0148] The battery cell 2 is placed in the shell 1 (prepared as described above), and the second end wall 12 and the shell 1 are connected together by laser welding; after drying, liquid is injected, formed, and constant volume is obtained to obtain a prepared lithium-ion battery.

[0149] X-ray fluorescence spectrometry

[0150] (1) Sample preparation: First, the stainless steel sample needs to be properly processed to facilitate X-ray penetration and stimulate fluorescence. This may include cutting, grinding, polishing and other steps to ensure that the sample surface is flat and free of contamination.

[0151] (2) X-ray excitation: High-energy X-rays are used to irradiate the sample surface to stimulate the characteristic X-ray fluorescence of each element. The wavelength or energy characteristics of these fluorescence spectra correspond to the type of element, so it is possible to determine which elements are contained in the sample.

[0152] (3) Spectrum collection and analysis: The X-rays reflected from the sample surface and the fluorescence spectrum emitted are collected by a spectrometer. The type and content of the element can be determined by the position and intensity of the characteristic spectral lines.

[0153] (4) Matrix effect correction: Due to the interaction between various elements in stainless steel (matrix effect), the collected spectral data needs to be corrected to eliminate the influence of this interaction on the analysis results and improve the accuracy of the analysis.

[0154] (5) Interpretation of results: Based on the corrected data, the content of each element in the stainless steel can be calculated, and then its performance and quality can be evaluated.

[0155] The measurement method of a is as follows:

[0156] Measure the height of the battery cell 2, i.e., the maximum distance a1 from the first end face to the second end face, and measure the height inside the shell 1, i.e., the minimum distance a2 from the first end wall to the second end wall. Measure three groups of data for each shell 1 and take the average value. The value of a is calculated by a=a2-a1.

[0157] The measurement method of d is as follows:

[0158] The thickness of the first end wall 11 is measured using an ultrasonic thickness gauge. During the measurement, three different positions of the first end wall 11 of each shell 1 are measured and the average value is taken as the thickness d of the first end wall 11 of the shell 1 .

[0159] Method for measuring the area of ​​the winding core hole 21:

[0160] The inner diameter of the winding core hole 21 is measured three times in different directions, and the average value is taken as the diameter k of the winding core hole 21. The formula S = π (k / 2) 2 , calculate the area S of the winding core hole 21.

[0161] The values ​​of a, d, and S of the prepared battery are shown in Table 1.

[0162] Embodiment 18-24:

[0163] Examples 18-24 are similar to Example 1, except that the battery cell 2 includes a positive electrode tab and a negative electrode tab, the positive electrode tab or the negative electrode tab is electrically connected to the housing 1, and the positive electrode tab and the negative electrode tab are arranged on the same end wall of the battery cell 2. The mass percentage of the Cr and the values ​​of a, b, c, d, and S of the prepared battery are shown in Table 2.

[0164] Embodiment 25-28:

[0165] Examples 25-28 are similar to Example 18, except that the positive electrode tab and the negative electrode tab are respectively arranged on the two end walls of the battery cell 2. The mass percentage of Cr and the values ​​of a, b, c, d, and S of the prepared battery are shown in Table 2.

[0166] Embodiment 29-38:

[0167] Examples 29-38 are similar to Example 1, except that Figure 3 As shown, the shell 1 is in the shape of a quadrangular prism.

[0168] This embodiment is similar to Embodiment 1, except that:

[0169] 1. The shell is prepared as follows:

[0170] (1) Preparation of steel: smelting the molten steel to remove impurities, and fine-tuning the target chemical composition required by the shell 1 to obtain the molten steel with the above-mentioned composition, and then casting to obtain a steel ingot;

[0171] (2) Preparation of blanks: rolling the steel ingot into coils, adjusting the size, gap and rotation speed of the rolling mill rolls to adjust the thickness of the coils during the rolling process, so as to prepare the shells 1 with different thicknesses d of the first end wall 11, and then cutting the coils into plates of appropriate sizes;

[0172] (3) Deep drawing: Place the sheet into a suitable die and fix it, then press the punch on the die with a certain force, replace the square die and punch to turn the circle into the square, and repeat the drawing until the shell 1 is formed. The formed shell 1 is a rectangular parallelepiped with a volume of 970000mm 3 .

[0173] (4) Trimming: Remove and trim the excess material during the deep drawing process to ensure that the burrs and flatness of the cut meet the requirements.

[0174] 2. Preparation of positive electrode

[0175] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O3, conductive agent acetylene black and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The system is stirred in a vacuum mixer until it becomes uniform to obtain positive electrode slurry. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain positive electrode sheets.

[0176] 3. Preparation of negative electrode sheet

[0177] The negative electrode active material artificial graphite, conductive agent (SP) and binder are mixed in a certain mass ratio (97:1:1), and deionized water is added as a solvent. The mixture is stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.

[0178] The values ​​of a, b, c, d, and S of the prepared battery are shown in Table 3.

[0179] Comparative Examples 1-3

[0180] Comparative Examples 1-3 are similar to Example 1, except that the values ​​of a, b, c, d, and S of the prepared batteries are as shown in Table 1.

[0181] Table 1

[0182]

[0183]

[0184] Table 2

[0185]

[0186]

[0187] Table 3

[0188]

[0189] Performance Test:

[0190] 1. Deformation degree of housing 1 after cyclic testing:

[0191] The lithium ion batteries prepared in the examples and comparative examples were subjected to cycle tests at 25° C. according to the following procedure, wherein when the positive electrode active material is nickel-cobalt-manganese ternary, the cycle strategy is as follows:

[0192] (1) Charge at a constant current rate of 1C to 4.35V, and charge at a constant voltage until the current drops to 0.05C;

[0193] (2) Let stand for 10 minutes;

[0194] (3) Discharge at 1C rate to 2.75V;

[0195] (4) Let stand for 10 minutes.

[0196] The test was repeated 50 times according to steps (1) to (4) to observe the height of the protrusion at the maximum deformation of the first end wall 11, wherein:

[0197] No deformation: deformation height is between 0-0.1mm;

[0198] Slight deformation: deformation height is between 0.1-0.5mm;

[0199] Moderate deformation: deformation height is between 0.5-1mm;

[0200] Severe deformation: greater than 1mm.

[0201] 2. Battery capacity test method:

[0202] Place the battery in a 25°C constant temperature box and perform the following operations on the test object:

[0203] (1) Charge at a constant current rate of 0.33C to 4.35V, and charge at a constant voltage rate until the current drops to 0.05C;

[0204] (2) Leave to stand for 30 minutes;

[0205] (3) Discharge at 0.33C to a lower voltage of 2.75V;

[0206] Repeat the above steps 3 times and take the discharge capacity of the third cycle as the battery capacity.

[0207] 3. Shell forming rate

[0208] The shell 1 is deep drawn and formed according to the above-mentioned preparation method of the shell 1, and the forming rate of 200 shells 1 is statistically prepared.

[0209] Comparative analysis of Examples 1-12, 29-38 and Comparative Example 1-3 shows that when 0.15≤a / [d×(b+c)]≤300 is satisfied, the shell 1 has a higher molding rate. At the same time, after 50 charge and discharge cycle tests of the battery, the deformation degree of the shell 1 caused by the expansion of the battery cell 2 is low, and the energy density of the battery is not too low. On this basis, when 1≤a / [d×(b+c)]≤200 is also satisfied, the molding rate of the shell 1 is higher.

[0210] When the shell 1 is cylindrical, when 1≤a / [d×(b+c)]≤200 is satisfied, 0.15<d<1.2mm, 0.5<a<10mm, 0.25<b+c<0.5wt.% is also satisfied, and the molding rate of the shell 1 is high and no deformation occurs. When the shell 1 is quadrangular prism, when 1≤a / [d×(b+c)]≤200 is satisfied, 0.15<d<1.2mm, 0.1<a<8mm, 0.25<b+c<0.5wt.% is also satisfied, and the molding rate of the shell 1 is high and no deformation occurs. Since the cylindrical shell 1 is most easily deformed due to the expansion of the battery cell 2 at the end wall, and the quadrangular prism battery shell 1 is most easily deformed due to the expansion of the battery cell 2 at the side wall 13 with the largest area, in order to make the shell 1 have a high forming rate and no deformation, the cylindrical shell 1 satisfies 0.5<a<10mm, while the quadrangular prism satisfies 0.1<a<8mm.

[0211] At the same time, when the shell 1 is in the shape of a quadrangular prism and the aspect ratio is greater than 2, that is, the shape change degree of the side wall 13 during the deep drawing process is relatively large, the plastic deformation ability required for its deep drawing forming is better, but the risk of deformation of the shell 1 due to the expansion of the battery cell 2 is higher. When b+c is 0.2-0.7wt.%, the deformation degree of the shell 1 is smaller while taking into account the forming rate of the shell 1.

[0212] It can be seen from Examples 13-17 that since the core hole 21 can be used as a gas storage space to reduce the expansion rate of the battery cell 2, when 0.4≤S×a≤600 is satisfied, the possibility of deformation of the housing 1 is reduced. When the area of ​​the core hole 21 is less than 0.4, the core hole 21 cannot store gas due to the small area of ​​the core hole, and the housing 1 is prone to deformation.

[0213] It can be seen from Examples 18-28 that excessive Cr content reduces the forming rate of the shell 1. When the positive and negative pole tabs are arranged at the same end of the battery cell 2, heat is concentrated, resulting in an increased risk of deformation of the end wall of the shell 1. To make the forming rate of the shell 1 high and prevent deformation, when the positive and negative pole tabs are arranged at the same end of the battery cell 2, a satisfies 0.5<a<10mm, and when the positive and negative pole tabs are arranged at the two ends of the battery cell 2, a satisfies 0.1<a<8mm.

[0214] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A battery, comprising a housing (1) and a battery cell (2) arranged in the housing (1), wherein the housing (1) is made of steel, and characterized in that: The battery is a quadrangular prism battery, the steel comprises Ti, Nb and Cr, wherein the mass percentage of Cr is ≥16wt.% based on the total mass of the steel; the shell (1) comprises a side wall (13) and an end wall, the end wall comprises a first end wall (11) and a second end wall (12) located at both ends of the side wall (13), and both ends of the battery cell (2) comprise a first end face close to the first end wall (11) and a second end face close to the second end wall (12); the first end wall (11) and the side wall (13) are integrally formed; The housing (1) satisfies the following relationship: 3≤a / [d×(b+c)]≤300; Wherein, a is the sum of the distance from the first end surface to the first end wall (11) and the distance from the second end surface to the second end wall (12), in mm; d is the thickness of the first end wall (11), in mm; b is the mass percentage of Ti based on the total mass of steel, in wt.%; c is the mass percentage of Nb based on the total mass of steel, in wt.%.

2. The battery according to claim 1, characterized in that The shell (1) satisfies the following relationship: 25≤a / [d×(b+c)]≤200.

3. The battery according to claim 1 or 2, characterized in that: The range of b+c is 0.2-0.8 wt.%.

4. The battery according to claim 3, characterized in that The range of b+c is 0.25-0.5 wt.%.

5. The battery according to claim 4, characterized in that The range of b is 0.05-0.2 wt.%.

6. The battery according to claim 1, characterized in that The range of c is 0.17-0.5wt.%.

7. The battery according to claim 1 or 2, characterized in that: The range of d is 0.15-1.2 mm.

8. The battery according to claim 1, characterized in that The range of a is 0.1-8 mm.

9. The battery according to claim 1, characterized in that When the aspect ratio of the shell (1) is not less than 2, the range of b+c is 0.2-0.7 wt.%.

10. The battery according to claim 1, characterized in that The battery cell (2) comprises a positive electrode tab and a negative electrode tab, wherein the positive electrode tab or the negative electrode tab is electrically connected to the shell (1), and the mass percentage content of Cr is 16-30 wt.%.

11. The battery according to claim 10, characterized in that The positive electrode tab and the negative electrode tab are both arranged on the first end face or the second end face of the battery cell (2), and the range of a is 0.5-10 mm.

12. The battery according to claim 10, characterized in that The positive electrode tab and the negative electrode tab are respectively arranged on the first end surface and the second end surface of the battery cell (2), and the range of a is 0.2-8 mm.

13. An electrical device, characterized in that: Comprising a battery as claimed in any one of claims 1 to 12.

Citation Information

Patent Citations

  • Battery and battery device

    CN218648033U

  • Battery

    CN221201265U

  • Battery cell and battery

    CN221632646U

  • Battery cell structure

    CN221900058U

  • Ferritic stainless steel material for battery components, method for producing same, and battery component

    WO2024070493A1

Cited By

  • Battery, battery module and battery pack

    CN120184402A

  • Battery, battery module, and battery pack

    CN120184402B